Preservation of Local Wisdom through the Batik Mangrove Project at SD Negeri 025 Teluk Binjai - Dewi Nurmala; Diana Wahyuni (WISE Pendidikan Indonesia, 2024)
This community service initiative at SD Negeri 025 Teluk Binjai addresses the need to enhance students' knowledge and skills related to Malay local wisdom and the mangrove ecosystem. The project aims to introduce students to the art of batik and the importance of preserving the mangrove ecosystem through the Batik Mangrove project. Using a descriptive qualitative method involving observation, interviews, and documentation, the project targeted fifth-grade students due to their cognitive ability to grasp ecosystem concepts and basic art skills. The activities included introducing the mangrove ecosystem, collaboratively designing batik inspired by mangrove flora and fauna, engaging in batik-making under the guidance of local artisans, and evaluating the impact through observations and interviews. The results indicated significant improvements in students' artistic skills, environmental awareness, and understanding of cultural preservation. This project also faced challenges such as limited curriculum time and initially low student interest in local culture. Future recommendations include involving more local elements, enhancing collaboration with stakeholders, and extending the project duration for greater impact. Ultimately, this initiative contributes to community well-being by fostering a generation that values and preserves local culture and the environment.